Microbiology cell-staining wastewater treatment using T iO 2 thin films (2015)
(Eng) Microbiology cell-staining wastewater was treated by UV/TiO 2 thin films photocatalysis. A simple method of applying gravity sedimentation over grass-type substrate was used for the preparation of the films. The use of Na4 P2 O7, microwaves, and ultrasounds were studied for decreasing the TiO2 grain sizes on the films. It was established that the best method for reducing grain size resulted from a combination of Na4P2O7 (0.01M) and microwave radiation (700 W, 20 min). The Films were characterized by several microscopic and spectroscopic methods. Anatase phase (gap energy of 3.2 eV) and grain sizes averaging 83 nm were achieved. Photocatalysis tests using TiO2-film showed 99.5 % of decolorization, 79 % TOC abatement, and total microbial inactivation after 14 h of treatment. No bacteria re–growth was found 48 h after the treatment was completed.